SAT-516 A Severe Case of Pembrolizumab-Induced Thyroiditis - Lane, Kyrstin (J Endocr Soc, 2020)
Pembrolizumab, a programmed death 1 (PD-1) inhibitor used for advanced malignancies, can be associated with thyroid dysfunction.(1-2) Specifically, thyroiditis occurs in nearly 2.3% of individuals.(2) The hyperthyroid phase is typically non-severe, requiring only beta blockers. Our case illustrates that conservative therapies may be ineffective in pembrolizumab-induced severe thyroiditis. A 54-year-old woman with metastatic non-small cell lung cancer with normal baseline TSH received pembrolizumab. She was hospitalized nearly 30 days later with nausea, vomiting and tachycardia. Labs showed TSH <0.02 mcIU/mL (normal 0.3-4.7), free T4 >7 ng/dL (normal 0.8-1.7) and free T3 2105 pg/dL (normal 222-383). TSH receptor antibody was undetectable; hyperthyroidism was attributed to pembrolizumab. Metoprolol was initiated. She was re-hospitalized three days later with persistent symptoms and inability to tolerate orals. Labs again showed severe hyperthyroidism and TPO antibody 201 IU/mL (normal ≤ 20). Burch-Wartofsky score was 25. Given her symptom severity, propylthiouracil, hydrocortisone, and propranolol were initiated to reduce peripheral T4 to T3 conversion. A cortisol of 5 mcg/dL (collected 9:47AM) further supported the use of hydrocortisone. Following a normal Cosyntropin stimulation test, hydrocortisone was discontinued. Her symptoms improved but hypothyroidism developed 68 days after pembrolizumab initiation. Propylthiouracil was discontinued; levothyroxine was started. Her TFTs ultimately normalized. Beta blockers are the mainstay of treatment of the hyperthyroid phase of PD-1 inhibitor-related thyroiditis, though case reports have described use of glucocorticoids, anti-thyroid drugs and iodine.(2 -4) In our patient, severe thyrotoxicosis was not responsive to beta blockers. Consideration of additional therapies is reasonable in these cases. References: 1. Puzanov I, Diab A, Abdallah K, Bingham CO 3rd, Brogdon C, Dadu R, Hamad L, Kim S, Lacouture ME, LeBoeuf NR, Lenihan D, Onofrei C, Shannon V, Sharma R, Silk AW, Skondra D, Suarez-Almazor ME, Wang Y, Wiley K, Kaufman HL, Ernstoff MS; Society for Immunotherapy of Cancer Toxicity Management Working Group. Managing toxicities associated with immune checkpoint inhibitors: consensus recommendations from the Society for Immunotherapy of Cancer (SITC) Toxicity Management Working Group. J Immunother Cancer. 2017 Nov 21;5(1):95. 2. de Filette J, Andreescu CE, Cools F, Bravenboer B, Velkeniers B. A Systematic Review and Meta-Analysis of Endocrine-Related Adverse Events Associated with Immune Checkpoint Inhibitors. Horm Metab Res. 2019 Mar;51(3):145-156. 3. Tan MH, Iyengar R, Mizokami-Stout K, Yentz S, MacEachern MP, Shen LY, Redman B, Gianchandani R. Spectrum of immune checkpoint inhibitors-induced endocrinopathies in cancer patients: a scoping review of case reports. Clin Diabetes Endocrinol. 2019 Jan 22;5:1.